Effect of drying, composting and subsequent impurity removal by sieving on the properties of digestates from municipal organic waste. (February 2018) - Knoop, Christine; Dornack, Christina; Raab, Thomas
Graphical abstract: Highlights: Composting of MOW digestates leads to nutrient and heavy metal accumulation. Heavy metal content increases with decreasing particle size of composted digestates. Nutrient, heavy metal and carbon elution from composted digestates is lower than from dried digestates. Elution of Zn, Ni, Ca and Mg significantly correlates with DOC and pH of eluate. DOC may be a good measure to evaluate digestate stability and to decide on treatment. Abstract: The application of organic soil amendments is a common measure to prevent structural degradation of agricultural soils and to maintain and improve long-term soil fertility. Solid residues from anaerobic digestion of municipal organic waste (MOW) are rich in nutrients and organic matter and have a promising potential to be used as soil amendment. However, no study has related amendment properties of MOW digestate of one origin to different treatment procedures. We therefore investigated the impact of drying, composting and sieving on final digestate properties and specifically nutrient availability and heavy metal and carbon elution. Samples were provided by a semi-industrial two-stage biogas plant with dry fermentation of MOW. Results confirm that in comparison to drying, composting of MOW digestates leads to a significant increase of K, P, Mg, Ca, Cd and Cr in the digestates. Sieving of composted digestates showed that heavy metals are not evenly distributed and that heavy metal concentration in the digestate increases with decreasing mesh sizes (highest concentrations in the fractions <1 mm). Although the element concentration is higher in composted batches, the water-extractability of nutrients, heavy metals and carbon is significantly lower from composted over dried digestates. A significant correlation was found between the dissolution of Zn, Ni, Ca and Mg and pH of eluate as well as dissolved organic carbon (DOC) release (R > 0.7, p < 0.05). Results confirm that the extent of carbon elution depends on the degradation rate of digestates. DOC may therefore be a good measure to evaluate digestate stability and to decide on treatment measures.